Rebranding pada Usaha Mikro Kecil Menengah Kopi Khas Kampung Budaya untuk Meningkatkan Penjualan dan Pemasaran - Arini, Iftitah; Levina Pridynafiah; Rindy Nur Fadhilah; Laksmi Diana, S.S, M.Pd (INCOME: Indonesian Journal of Community Service and Engagement, 2022)
To face the digital world, new innovations are needed in order to continue to grow in difficult times, including keeping up with the times and technology. In this case, intervention from various parties is really needed to be able to provide mentoring to MSMEs in order to move towards the era of Advanced Digital MSMEs in Indonesia because MSMEs must have a patent identity. The problem that SMEs (Micro, Small and Medium Enterprises) may experience is a lack of understanding of branding. One of them is MSMEs Typical Coffee Powder of Kampung Budaya as MSME partners who receive mentoring for rebranding activities. After the rebranding process was carried out, the UMKM Typical Kampung Budaya Coffee Powder will continue to grow in the future, maybe slowly, but giving positive results. Especially after updating logos, packaging, utilizing social media and sales channels such as introducing via whatsapp business and websites and then registering at start-ups such as Tokopedia and providing electronic payment services through online payment platforms that make everything closer and easily accessible to the public so that this helps MSMEs Typical Kampung Budaya Coffee Powder to continue to exist and grow in the future.